The Real and the Surreal: Two approaches to social criticism in the plays of Gholam-Hosayn Saʿedi - Kapuscinski, Gisèle (Gesellschaftlicher Umbruch und Historie im zeitgenössischen Drama der islamischen Welt, 1995)
The article introduces the works of Gholam-Hosayn Sa'adi who in the 1960ies and 70ies had been one of Iran's leading dramatists. In 1979 he emigrated to Paris where he remained until his death in 1985. Besides a playwright he had been a political activist and for some time had worked as a psychiatrist. Accordingly his works deal with socio-political themes. Socio-political themes which apply to twentieth century Iran but which Sa'adi in close observation of human nature manages to transcend to the universal level. (DÜI-Mjr)